(untitled) - 1949-; Hewitt, David; Hewitt, Kathryn (New York, 2008)
Follows Uncle Sam as he rallies the country during the War of 1812, welcomes immigrants at the turn of the twentieth century, gives hope to Americans during the Great Depression, and helps the people of the United States fulfill their dreams and create a better nation.
Keywords: American national characteristics; National emblems; United States; History